PERANAN KELOMPOK TANI DALAM PEMANFAATAN MADU LEBAH HUTAN DI DESA SAHILAN DARUSSALAM KECAMATAN GUNUNG SAHILAN KABUPATEN KAMPAR PROVINSI RIAU - Wispinaldo, Azhari; Marhiansyah, M.; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The sustainable management wild honey requires an organization, mainly to ensure the quality standard of naturalness of the wild honey and preserve the beehive trees by forming a farmers group. This research aims to find out the role of the farmers group in the utilization of wild honey in Sahilan Darussalam Village, Gunung Sahilan District, Kampar Regency, Riau Province. This research was conducted from November up to December 2015. The data collection method used in this research is census, defined as a data collection method where whole of the population elements are known one by one. The data are gained from the census processing result, called as true value or parameter. Analysis of qualitative descriptive is an analysis by describing the whole event of the research objects and elaborate it accordance to the data and the facts on the ground. The research findings show three roles of the farmers group in the utilization of wild honey in Sahilan Darussalam Village, Gunung Sahilan District, Kampar Regency, Riau Province, those are the role in the institution, production, and capital. Firstly, the role of the farmers group in terms of institution is to increase monthly income and to make it easy in joining programs of the development of wild honey supported by the government.Â Secondly, in terms of production, it is to maintain the production quality by applying a leak system. Thirdly, in terms of capital, it is to gain a main capital in a way of self-sufficiency from the members.Key words: role, farmers group and honey.